The influence of the COVID-19 Pandemic on the Construction Technology works - Dorin MAIER (Communications of International Proceedings, 2021)
The current global situation is still marked by the unexpected appearance, at the beginning of 2020, of the SARS COV 2 virus. The entire society has been affected without taking into account any criteria, be it financial or human. The purpose of this paper is to identify and analyze the effects of the COVID-19 pandemic on one of the most important sectors of activity in society, namely the construction sector. In this sense the research started with the identification of the main effects of the pandemic on the entire society. The next step was to highlight the main particularities and vulnerabilities of the construction industry in front of the pandemic. The final step was to present the future trends and solution to recover after the pandemic for the construction industry.
Keywords: Covid-19 Pandemic; Construction Technologies; Civil Engineering Works; Civil Engineering